The Effect of Household Drinking Water Quality on the Incidence of Toddler Diarrhea in Densely Populated - Miskha Syafa; Adrenalin Faysazahra (Generasi Sains Indonesia, 2025)
This study investigates the relationship between household drinking water quality and the incidence of toddler diarrhea in densely populated areas of Manado City, Indonesia. A quantitative cross-sectional approach was employed involving 500 households with children under five years of age. Data were collected through household surveys, laboratory-based water quality testing, and validation using local health facility records. The findings reveal that households relying on groundwater wells experienced significantly higher levels of microbial contamination, particularly Escherichia coli, compared with households using piped water systems. Toddler diarrhea incidence was substantially higher among households consuming untreated water and those dependent on contaminated groundwater sources. Statistical analysis confirmed that water source and household water treatment practices were significant predictors of diarrhea occurrence. The findings contribute to environmental health literature and provide evidence for strengthening water safety interventions, sanitation improvement programs, and community-based public health strategies aimed at reducing childhood waterborne diseases in rapidly urbanizing cities.